Nitrogen, phosphorus co-doped carbon dots/CoS2 hybrid for enhanced electrocatalytic hydrogen evolution reaction. Issue 71 (13th July 2016) - Wang, Liping; Zhao, Shunyan; Wu, Xiuqin; Guo, Sijie; Liu, Juan; Liu, Naiyun; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : A nitrogen, phosphorus co-doped carbon dots/CoS2 hybrid was synthesized as electrocatalyst for hydrogen evolution reaction with desirable electrocatalytic activities (low overpotential ∼78 mV, small Tafel slope ∼76 mV dec −1 ) and long-term stability in acidic media. Abstract : Developing highly efficient and low cost hydrogen evolution reaction (HER) electrocatalysts is still a huge challenge. In this study, we demonstrate a facile method to fabricate a nitrogen, phosphorus co-doped carbon dots/CoS2 (NPCDs/CoS2 ) hybrid as an electrocatalyst for HER with desirable electrocatalytic activities (low overpotential ∼78 mV and small Tafel slope ∼76 mV dec −1 ) and long-term stability (after 1000 CV cycles with negligible current loss ∼1 mA cm −2 ) in acidic media.